2021
DOI: 10.1016/j.chemosphere.2021.130567
|View full text |Cite
|
Sign up to set email alerts
|

Ternary metal oxide embedded carbon derived from metal organic frameworks for adsorption of methylene blue and acid red 73

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…38 Yu et al used CMOF(Fe/Al/Ni 8/7/5)-NH 2 for the adsorption of MB and Acid Red 73, and equilibrium was attained in 30 min at a neutral pH. 55 Jaseela et al synthesized organic–inorganic hybrid nanocomposites of TiO 2 -PVA using a sol–gel method and utilized it for the selective adsorption of MB dye from the mixture of MB and MO. 39…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Yu et al used CMOF(Fe/Al/Ni 8/7/5)-NH 2 for the adsorption of MB and Acid Red 73, and equilibrium was attained in 30 min at a neutral pH. 55 Jaseela et al synthesized organic–inorganic hybrid nanocomposites of TiO 2 -PVA using a sol–gel method and utilized it for the selective adsorption of MB dye from the mixture of MB and MO. 39…”
Section: Resultsmentioning
confidence: 99%
“…38 Yu et al used CMOF(Fe/Al/ Ni 8/7/5)-NH 2 for the adsorption of MB and Acid Red 73, and equilibrium was attained in 30 min at a neutral pH. 55 Jaseela et al synthesized organic-inorganic hybrid nanocomposites of TiO 2 -PVA using a sol-gel method and utilized it for the selective adsorption of MB dye from the mixture of MB and MO. 39 The simple method of synthesis at a low temperature and a single component metal oxide without any capping agent makes the SnO 2 QD 2 unique and cost-effective compared to other reported method.…”
Section: Njc Papermentioning
confidence: 99%
“…The kinetics study was conducted by agitating the CR solution at room temperature with an initial concentration of 80 mg L −1 and C-V-1 dosage of 10 mg. Several kinetic models, including the quasi-first-order kinetic model, pseudo-second-order, intra-particle diffusion model, and Elovich model were employed to simulate the adsorption of CR onto C-V-1. 63,64 Fig. 5e and f reveals the tem-poral evolution of the absorbance of CR aqueous solution adsorbed by C-V-1.…”
Section: Papermentioning
confidence: 99%
“…The embedded NiO was recognized as the anionic adsorption site for MB, while α-Fe 2 O 3 and γ-Al 2 O 3 were recognized as cationic adsorption sites for AR-73. 31 In addition, our recent study demonstrated that the incorporation of Mo atoms as a second metal source into layered carbon nanostructures via pyrolysis from the catalyst precursor of a Cu-based MOF could modify the adsorption performance. 32 Based on the above considerations, a Cu-based complex {[Cu 3 (4-bpah)(CHDA) 3 (H 2 O)]•2H 2 O} n (1), where 4-bpah denotes N,N′-bis(4-pyridinecarboxamide)-1,2-cyclohexane and H 2 CHDA denotes 1,4-cyclohexanedicarboxylic acid, was synthesized in this study and structurally characterized by single-crystal X-ray diffraction (SCXRD), infrared (IR) spectroscopy, and powder X-ray diffraction (PXRD).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, "the adsorption technique is well used due to its simple operation conditions and chemical removal efficacy. The adsorption method has been carried out using several adsorbents such as metal oxides, chitosan, graphene, graphene oxides, and activated carbons" [11][12][13][14][15]. To reduce the water treatment price, adsorbents from agricultural byproducts were used by many researchers [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%